The impact of brand familiarity on brand credibility and perceived quality of brands Marhen. J : an empirical analysis - Saputri, Kurnia Dwi; Fany Safriyanti; Lingga Yuliana (SEAN Institute, 2024)
The purpose of this study is to examine, using the Marhen. J brand as a case study, the effects of brand familiarity on perceived quality and brand credibility. Methods of quantitative description are used in this study. The present study employed purposive sampling, whereby participants were selected based on their familiarity with the Marhen J bag brand. In all, one hundred respondents took part in this study. Partial Least Square is used as data analysis in research and processed using the Smart PLS analysis tool version 3.3.9. The research results show that the first hypothesis shows the influence of Brand Familiarity on Brand Credibility. And the second hypothesis shows that there is an influence between Brand Familiarity on Perceived Quality. The managerial implication in this research is that a brand will be more closely remembered by consumers if the brand owner is also involved in marketing and is better known to the public. With limited sales places for the Marhen. J brand, it is also an obstacle for people to get to know and buy Marhen. J bag products and services. Therefore, the Marhen. J brand must be able to expand its market share so that its products can be reached by many groups.